Binding mechanism of Cr(PLB)3 and Hg(PLB)2 complexes with human serum albumin: Spectroscopic, thermodynamic, and molecular docking investigations - Nguyen Van Thoi; Tran Khanh Luan; Tran Phuoc Vy; Tran Nguyen Minh An; Le Van Tan (Results in Chemistry)
Plumbagin (PLB) and its metal complexes are of pharmacological interest due to their potential biomedical applications. This study systematically investigates, for the first time, the interactions of Cr(PLB)₃ and Hg(PLB)₂ complexes with human serum albumin (HSA) using UV–Vis, FT-IR, NMR, fluorescence, circular dichroism (CD) spectroscopy, and thermodynamic analyses. Both complexes bind at site IIA of HSA, with binding constants (Kb) of 3.8 × 104 L/mol for Cr(PLB)₃ and 2.5 × 104 L/mol for Hg(PLB)₂. Their binding perturbs the Trp214 environment and reduces the α-helical content of HSA from 62 % to 55 % (Cr) and 57 % (Hg). FRET analysis estimated the donor–acceptor distance to be approximately 2.5 nm. Thermodynamic data revealed that the Cr(PLB)₃–HSA interaction is enthalpy-driven (ΔH = −3.7 kcal/mol, ΔS = +8.7 cal/mol. K), while the Hg(PLB)₂–HSA interaction is also enthalpy-driven but with negligible entropy change (ΔH = −5.2 kcal/mol, ΔS = +0.7 cal/mol.K). Molecular docking suggested hydrogen bonding, van der Waals, and hydrophobic interactions as key forces, with Cr(PLB)₃ showing stronger binding affinity. These findings offer insight into the interaction mechanisms of metal–PLB complexes with HSA, supporting their further biomedical evaluation.